A discriminatory study of a pharmacokinetic model for intramuscular gentamicin in sheep - Errecalde, Jorge Oscar (1990)
The resulting serum concentrations were measured in six ewes after intramuscular administration of 10 mg/kg of gentamicin. The model providing the best fit for the experimental data was determined both by linear regression analysis between the experimental and theoretical values and by means of the Minimum Akaike Information Criterion Estimation (MAICE) test. Linear regression analysis showed certain differences favouring the monocompartmental model although the advantage was not conclusive. The MAICE test, however, permitted a clear discrimination in favour of the same model. When linear regression analysis is not conclusive, the MAICE test represents a good alternative.